2020
DOI: 10.1002/cam4.3404
|View full text |Cite
|
Sign up to set email alerts
|

The impact of orthotopic neobladder vs ileal conduit urinary diversion after cystectomy on the survival outcomes in patients with bladder cancer: A propensity score matched analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…However, due to the complexity of the combined surgery, the long operation time, and the large trauma to the patient's body, the incidence of postoperative complications is at a high level, which is detrimental to the patient's postoperative recovery and adversely affects the surgical outcome. Therefore, finding reliable indicators to predict the incidence of postoperative complications in patients with bladder cancer has become one of the hot spots in clinical research [ 6 ].…”
Section: Prefacementioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the complexity of the combined surgery, the long operation time, and the large trauma to the patient's body, the incidence of postoperative complications is at a high level, which is detrimental to the patient's postoperative recovery and adversely affects the surgical outcome. Therefore, finding reliable indicators to predict the incidence of postoperative complications in patients with bladder cancer has become one of the hot spots in clinical research [ 6 ].…”
Section: Prefacementioning
confidence: 99%
“…erefore, nding reliable indicators to predict the incidence of postoperative complications in patients with bladder cancer has become one of the hot spots in clinical research [6].…”
Section: Prefacementioning
confidence: 99%
“…Consequently, we believe that the type of diversion would work as a confounding variable rather than a predictor. In a recent study comparing the type of urinary diversion on survival outcomes, the authors have found that a young man with early disease was likely to receive orthotopic neobladder and hence achieved a better survival [ 28 ]. However, validation in other types of urinary diversion will ensure the broader applicability of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Convincing evidence suggests that compared to the non-continent conduit method, continent orthotopic neobladder offers a better quality of life (QoL) and greater physical function while having comparable oncologic outcomes ( 1 – 4 ). Despite the promising results, the worldwide trend of orthotopic neobladder performance is currently in the stationary phase, and it is at least partly due to considerable early phase complication rates in orthtotopic neobladder patient group ( 3 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%